Crescimento de jabuticabeiras açu produzidas em diferentes intensidades luminosas e cultivadas em distintas condições de acidez do solo - Hossel, Cristiano (2019)
The jabuticaba treebelong to the Myrtaceae family and Pliniagenus. There are about nine species of jabuticaba tree. Among these species are Plinia trunciflora(jabuticabatreede cabinho), which occurs naturally in the Southwest region of Paraná, Plinia cauliflora(jabuticabatreepaulista or jabuticaba tree açu) and Plinia jaboticaba(Vell) (jabuticaba tree sabará) that produce fruits to use in theindustry orin natura consumption. The objective of this work was to verify the effect of soil pH on the survival and initial growth of jabuticaba tree(Plinia cauliflora) atorchard, after they to beproduced in different conditions of shading and ofseedlings obtained by mini-cuttings. The work was carried out in the Orchard of Native Fruits and in the Teaching and Research Unit of Nursery, of the Federal Technological University of Paraná (UTFPR) -Câmpus Dois Vizinhos –Paraná State. Two experiments were carried out, one in the field with already formed plants, about three years old and the other with seedlings from the two-year-old from mini-cutting. Experiment 1 was implanted in a randomized block design, in a 4 x 5 x 3 factorial (season x shade during seedling production x soil pH), with 4 blocks and 3 plants per experimental unit. The jabuticaba treeseedlings were formed in full sun, side cover with 80% and superior shading screen with clear plastic, side and top cover with 50% shading, side and top cover with 90% shade and lateral and top cover with 35% shading screen. The pH was corrected to 5.5; 6.5 and 7.5. For experiments 1 and 2, monthly measurements of stem height (cm), crown height (cm), total height (cm), trunk diameter at plant height in two quadrants (cm), number and length of new shoots and total number of new leaves and later, with these results the means were performed according to each season of the year, in 2017 and 2018. For experiment 1, leaf area evaluations (cm²), leaf length and width (cm)and the relative content of chlorophylls a, b and total. Experiment 2 was implanted in a completely randomized design, in factorial 4 x 6 (evaluation month x amount of limestone), with 4 replications and 5 plants per experimental unit. The seedlings were planted in 4-liter pots containing red latosol. Shell limestone was applied for the pH correction in the amounts of 1, 2, 4, 6 and 8 t ha-1, besides the control (without application). At the end of the experiment, shoot length (cm), stem diameter (mm), total number of leaves, root mean number and length (cm), aerial (g) and root dry mass (g) and Dickson's Quality Score (IQD). It was concluded that initial shading during the formation of jabuticabaseedlings interferes after with its morphologyduring cultive at orchard. The seasons spring and summer showedgreater growth of the plantsat orchard. The application of limestone promoted elevation of pH of the soil, but did not present significant in the growth of the jabuticaba treesin the orchard. The applications of limestone had effect significant to jabuticaba seedling formation with amounts between 5 and 6 t ha-1.